Australian and Thai Isolates of Burkholderia pseudomallei Are Distinct by Multilocus Sequence Typing: Revision of a Case of Mistaken Identity - J. Currie, Bart (American Society for Microbiology (ASM), 2007)
A recent study using multilocus sequence typing (MLST) of Burkholderia pseudomallei isolates found a sequence type (ST60) to be common to both Thailand and Australia, contradicting earlier studies showing complete distinction between isolates from these regions. The ST60 isolates reportedly from Australia had been obtained for MLST from United Kingdom and U.S. collections. We have located and characterized the original Australian isolates; they were collected in 1983, and they are neither ST60 nor B. pseudomallei isolates. The B. pseudomallei MLST database has been corrected, and there is no ST common to isolates verified as obtained from Australia or from Thailand.